Management of Bos Fund Utilization to Support Technology-Based Education Quality - Mu’awinah, Ajnihatin; Nurkolis, Nurkolis; Muhtarom, Muhtarom (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
Educational quality is influenced not only by learning outcomes but also by how effectively schools manage financial resources to support instructional processes, including the integration of learning technology. This study examines the management of School Operational Assistance (BOS) funds in supporting technology-based education quality at SDN Dersansari 02, Semarang Regency, Indonesia. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis involving 11 key informants, including school leaders, teachers, students, and education authorities. Data were analyzed using an interactive qualitative analysis model consisting of data collection, condensation, display, and conclusion verification, supported by source and method triangulation. The findings indicate that effective management of BOS funds guided by the principles of transparency, accountability, effectiveness, and efficiency has significantly contributed to the availability, sustainability, and utilization of learning technologies, such as digital learning media, internet infrastructure, and technology-based assessment tools. Transparent budgeting and accountable reporting strengthened stakeholder trust, while effective and efficient allocation ensured that technology investments directly supported instructional quality and digital assessment implementation. This study contributes to the literature on educational finance and technology integration by demonstrating how structured BOS fund management can serve as a practical financing model for enhancing technology-based learning quality at the elementary school level.